PENGARUH ENTREPRENEUR PERSONALITY TERHADAP ENTREPRENEURIAL PERFORMANCE PADA IBU RUMAH TANGGA DI DESA TANJUNG KARANG KECAMATAN BATURAJA BARAT KABUPATEN OKU - Iis Mardiana; Harby Wiralaga; Yopi Yunsepa (KOLEGIAL, 2022)
This research objective is to figure out The Affect of Entrepreneur Personality on Entrepreneurial Performance of Housewives in Tanjung Karang Village, Baturaja Barat District, OKU Regency by employing a descriptive method. Whereas, the samples are 41 housewives living in Tanjung Karang Village, Baturaja Barat District, OKU Regency. The equation of simple linear regression model shows , i.e. Y = 3,517 + 0,743X, and correlation value is 0,618, hence the correlation value of Entrepreneur Personality on Entrepreneurial Performance is strong. The value of coefficient determination yield by the R